2000
DOI: 10.1002/1097-4652(200011)185:2<174::aid-jcp2>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human monocyte proMMP-9 production by fetuin, an endogenous TGF-? antagonist

Abstract: Members of the matrix metalloproteinase family of enzymes degrade specific components of the extracellular matrix. MMP-9 is a type IV/V collagenase necessary for normal osteogenesis and is increased in inflammatory and neoplastic conditions. In such destructive diseases as emphysema and arthritis, and in epithelial cancers, MMP-9 is produced by cells of the monocyte lineage. Fetuin, a prominent serum glycoprotein, binds to and inactivates TGF-beta family members and through this mechanism regulates osteogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Furthermore knockout mouse models directly demonstrate that deficiency of MMP-9 is related to reduced aneurysm formation (Pyo et al, 2000) and impaired monocyte migration (Ducharme et al, 2000). As previously described, cytokines, LPS, or phorbol esters can induce the secretion of MMP-9 using different cells such as murine (Yoo et al, 2002) and human monocytes (Shu et al, 2000;Tajirian et al, 2000), renal cells (Eberhardt et al, 2002), intestinal epithelial cells (Gan et al, 2001), and smooth muscle cells (Marx et al, 1998a). Although MMP secretion has been widely studied in several cell types, they are less well understood in macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore knockout mouse models directly demonstrate that deficiency of MMP-9 is related to reduced aneurysm formation (Pyo et al, 2000) and impaired monocyte migration (Ducharme et al, 2000). As previously described, cytokines, LPS, or phorbol esters can induce the secretion of MMP-9 using different cells such as murine (Yoo et al, 2002) and human monocytes (Shu et al, 2000;Tajirian et al, 2000), renal cells (Eberhardt et al, 2002), intestinal epithelial cells (Gan et al, 2001), and smooth muscle cells (Marx et al, 1998a). Although MMP secretion has been widely studied in several cell types, they are less well understood in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are regulated at several levels: transcription, activation of the inactive zymogens (pro-MMPs), and inhibition of proteolytic activity by tissue inhibitors (TIMPs). In vitro experiments have shown that phorbol esters, lipopolysaccharides or cytokines can stimulate MMP secretion (Shu et al, 2000;Tajirian et al, 2000;Yoo et al, 2002). In vivo, plasmin is a potent proenzyme activator, but alternative pathways can exist such as autocatalyzation of the cleavage of the propeptide.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, although considered as a powerful inflammation suppressor, TGF-␀ is equally recognized for its proinflammatory properties in certain conditions (46). In particular, in vitro treatment of monocytes with TGF-␀ stimulated TNF-␣, IL-1␀, and MMP9 release and decreased MSR-1 expression (14,41,55,61,66), thus promoting their maturation into M1 macrophages (3). Taken together, a decreased release of CCL2, IL-6, and CCL17 associated with an increased secretion of TGF-␀ may explain the preferential differentiation of THP-1 cells into inflammatory macrophages in response to FSS stimulated-HK-2 cells.…”
Section: Profiling Of Inflammation-related Factors In Fss-cmmentioning
confidence: 99%
“…␣2-HS-glycoprotein (Ahsg)/ fetuin is a glycoprotein present in serum and extracellular matrix that binds to TGF-␀ cytokines (bone morphogenetic proteins 2, 4, and 6 and TGF-␀1 and TGF-␀2) via a 19 amino acid cytokine-binding domain homologous to an extracellular sequence in the T␀RII (26). Ahsg antagonized binding of TGF-␀1 to T␀RII in surface plasmon resonance assays and inhibited the effect of TGF-␀1 on mink lung epithelial cell proliferation, rat bone marrow cell osteogenic differentiation (27), and human monocyte matrix metalloproteinase 9 release (28). Ahsg and TGF-␀1 are also concentrated in mineralized bone, and Ahsg ÏȘ/ÏȘ mice display a bone phenotype characterized by increased trabecular bone remodeling, osteoblast density, femur thickness, and bone mineral density (29).…”
Section: Introductionmentioning
confidence: 99%